Dual or Not Dual?—Comparative Analysis of Fluorescence Microscopy-Based Approaches to Study Organelle Targeting Specificity of Nuclear-Encoded Plant Proteins - Sharma, Mayank; Bennewitz, Bationa; Klösgen, Ralf Bernd (Frontiers in Plant Science, 2018)
Plant cells are unique as they carry two organelles of endosymbiotic origin, namely mitochondria and chloroplasts (plastids) which have specific but partially overlapping functions, e.g., in energy and redox metabolism. Despite housing residual genomes of limited coding capacity, most of their proteins are encoded in the nucleus, synthesized by cytosolic ribosomes and need to be transported "back" into the respective target organelle. While transport is in most instances strictly monospecific, a group of proteins carries "ambiguous" transit peptides mediating transport into both, mitochondria and plastids. However, such dual targeting is often disputed due to variability in the results obtained from different experimental approaches. We have therefore compared and evaluated the most common methods established to study protein targeting into organelles within intact plant cells. All methods are based on fluorescent protein technology and live cell imaging. For our studies, we have selected four candidate proteins with proven dual targeting properties and analyzed their subcellular localization in vivo utilizing four different methods (particle bombardment, protoplast transformation, Agrobacterium infiltration, and transgenic plants). Though using identical expression constructs in all instances, a given candidate protein does not always show the same targeting specificity in all approaches, demonstrating that the choice of method is important and depends very much on the question to be addressed.